2019
DOI: 10.1071/pc18079
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked and undervalued: the neglected role of fauna and a global bias in ecological restoration assessments

Abstract: Globally increasing rates of mine site discontinuations are resulting in the need for immediate implementation of effective conservation and management strategies. Surveying vegetation structure is a common method of assessing restoration success; however, responses of fauna to mine site restoration remain largely overlooked and understudied despite their importance within ecosystems as ecological engineers, pollinators, and restoration facilitators. Here we review the current state of the use of fauna in asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 63 publications
0
45
0
4
Order By: Relevance
“…We found few examples of fauna monitoring using UAVs in a restoration context, potentially reflecting the global paucity of literature relating to fauna recovery following disturbance [55]. However, RGB-equipped UAVs have been employed to assess distribution and density in fauna species that are challenging to survey on foot, such as orangutan (Pongo abelii) [56] and seabird colonies [57,58].…”
Section: A Need To Realise the Full Potential Of Uav Platforms And Sementioning
confidence: 99%
“…We found few examples of fauna monitoring using UAVs in a restoration context, potentially reflecting the global paucity of literature relating to fauna recovery following disturbance [55]. However, RGB-equipped UAVs have been employed to assess distribution and density in fauna species that are challenging to survey on foot, such as orangutan (Pongo abelii) [56] and seabird colonies [57,58].…”
Section: A Need To Realise the Full Potential Of Uav Platforms And Sementioning
confidence: 99%
“…Historically, there has been an emphasis placed upon assessing vegetation structure and community dynamics in post-restoration monitoring (Ruiz-Jaen & Mitchell Aide 2005;Koch et al 2010). Consequently, animal taxa are often overlooked in assessments of restoration success (Lindell 2008;Cross et al 2019;2020a) despite their role in providing critical ecological services, such as soil decomposition (Jouquet et al 2006;Lavelle et al 2006), pollination (Phillips et al 2010;Menz et al 2011;Frick et al 2014) and regulation of predator-prey dynamics (Mace et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous calls for fauna to receive greater consideration in restoration projects (Majer ; Lindell ; Majer ; Cross et al ). While some studies report on the responses of fauna to landscape revegetation, for example in agricultural areas of Australia (Munro et al ), the poor representation of fauna in studies of ecosystem recovery continues to be reported across numerous landscape degradation processes, including broadacre agriculture (McAlpine et al ; Catterall ), forestry (Jansen ; Rodrigues et al ), mining (Cross et al ) and the creation of novel ecosystems, for example through climate change (Kennedy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Summarised as the Field of Dreams Hypothesis, or ‘build it and they will come’ (Palmer et al ; Cristescu et al ), this assumption is appealing in theory and seems to be entrenched in the attitudes of practitioners to ecosystem recovery. However, this theory fails to recognise critical plant–animal interactions that are integral to ecosystem function (Tomlinson et al, ), and few studies have rigorously tested whether fauna from different functional groups do return to restored ecosystems (Hale et al ; Cross et al ). While some studies assess faunal responses to variation in habitat conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation